Incidence of Educational Management and Cultural Diversity on the Educational Quality (Docentes 2.0 Journal, 2025)
Quality in the educational field acquires relevance to the extent that it is oriented towards satisfying educational needs, understood not only from a perspective of academic progress but also in its relationship with the processes of continuous transformation of the educational system and multicultural diversity. The objective of the research was to determine the impact of educational management and cultural diversity on the educational quality of teachers in an educational network in San Juan de Miraflores, Metropolitan Lima-2023. Regarding the methodology, there was an approach with a hypothetical deductive method, a positivist paradigm, a quantitative approach, and a non-experimental design of a cross-sectional causal correctional type. A sample of 186 teachers of Regular Basic Education was worked with. Three instruments were used to measure Educational Quality, Educational Management, and Cultural Diversity, whose results were processed through the Pseudo-R-Square statistics; according to the McFadden test, it was concluded that pedagogical management and cultural diversity affect 7.6% of educational quality. In short, it was possible to confirm the impact of 77.9% of the variables of educational management and cultural diversity on the variable educational quality.
Keywords: Quality of education; intercultural education; educational management; educational efficiency; teacher effectiveness